Romania: Between Scylla of EU Law and Charybdis of National Interest – Belated Restrictions in the Land Market - Veress, Emőd (Acquisition of Agricultural Lands, 2022)
The cross-border acquisition of agricultural lands in Romania was subject to recent modifications. The regime of the circulation of agricultural lands after the EU accession of this country was designed through the provisions of Act no. 17/2014 on some measures to regulate the sale of agricultural land located outside the built-up area. The act was adopted to ensure food security and protect national interests in the exploitation of natural resources. These goals are perfectly justified and foreshadow changes in the global environment that will affect social and economic arrangements in the future with great impact. Protecting agricultural land as a natural resource of central importance is a legitimate goal. However, the methods used must be carefully chosen to create a legal regime for the sale of agricultural land that both respects the requirements of European law and conforms to the national interest as far as possible. The current system, created by amending Act no. 17/2014 into Act no. 175/2020, in force since October 13, 2020, shaped a legal regime that raises more questions than the answers it offers to the real challenges outlined above.Keywords: Romania, agricultural land, forestry land, preemption rights, precontracts, prior authorizationof selling